Bolus Detection in the Proximal Esophagus Using Pulse‐Echo Ultrasound: A Feasibility Study. (5th May 2020) - Wilcox, Andrew; Jackson, Daniel; Jones, Joshua; Thomas, Samuel
Abstract : Here, the feasibility of using nonimaging pulse‐echo ultrasound as a method of noninvasively detecting a bolus in the proximal esophagus was demonstrated. To accomplish this, patient swallows were recorded on a clinical ultrasound device with research interface that allowed for collection of the pulse‐echo data. These ultrasound data of the proximal esophagus were processed with a series of signal processing techniques in both the temporal and spectral domains, which revealed characteristic signatures that were unique for both liquid and food boluses compared to the normal collapsed esophageal state. Since substantial amounts of laryngopharyngeal reflux are gaseous in nature, future work will revolve around expanding the data set to include boluses of gaseous refluxate, a standardized methodology for capturing bolus events; developing automated detection tools for identifying laryngopharyngeal reflux for an extended duration; and assessing technology limitations due to user error.